Kajian Sosial Ekonomi Beberapa Varietas Unggul Baru Padi di Lahan Sub-Optimal Gunungkidul, Yogyakarta - Sugeng Widodo; Bambang Sutaryo; Damasus Riyanto (Seminar Nasional Lahan Suboptimal, 2018)
Widodo et al, 2019. Social Economic Studies of Several New Superior Rice Varieties on Sub-Optimal Area in Gunungkidul, Yogyakarta. pp. 456-464. This research aimed to analyze social economic studies of several new superior rice varieties on sub-optimal area in Gunungkidul, Yogyakarta. Social Economic studies on several new rice superior varieties on sub-optimal area has been implemented in “Gabungan Kelompok Tani Kumpul Makaryo, Nglanggeran, Patuk, Gunungkidul Yogyakarta from February to June 2018. New superior rice  varieties such as  Inpago 5, Inpago 8, Inpago 10, Inpari 42 Agritan GSR, Inpari 43 Agritan GSR and a check variety namely Ciherang were used in this study. Economic data input and output were analyzed for it’s feasibility of farming (B/C ratio). Organoleptic tests carried out by the level of preference as much as 25 repondens.Variabel panelists assessed texture / kepulenan, flavor, aroma, color and joy in general. Data indicated that those new five superior rice varieties feasible to develop proven B / C ratio ranged from 2.02 for Inpari 43 GSR to 2.90 for Inpari 42 GSR. Meanwhile, Ciherang as a populair variety gave B/C ratio only 1.88 . The most preferred taste of rice was Inpari 42 GSR and Inpago 5. While the productivity of the most preferred were Inpari 42 GSR and Inpago 10. It was suggested that those new rice superior varieties above mentioned must be developed in rainfed areas other than Nglanggeran-Patuk, to achieve increasing rice production in Gunungkidul dry land.